2018
DOI: 10.1053/j.gastro.2018.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Budesonide, vs Mesalazine or Placebo, as Induction Therapy for Lymphocytic Colitis

Abstract: In a randomized multicenter study, we found oral budesonide 9 mg once daily to be effective and safe for induction of clinical and histologic remission in patients with lymphocytic colitis, compared with placebo. Oral mesalazine 3 g once daily was not significantly better than placebo. ClinicalTrials.gov no: NCT01209208.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 34 publications
2
52
0
2
Order By: Relevance
“…89 HRQoL was evaluated in five RCTs including CC patients [189][190][191][192][193][194] and in two RCTs including LC patients. 192,195 In all seven RCTs, HRQoL was markedly altered at baseline in both CC and LC patients, and improved after budesonide treatment. [196][197][198] Are there established metrics to measure disease activity and clinical remission in MC?…”
Section: Very Lowmentioning
confidence: 99%
See 3 more Smart Citations
“…89 HRQoL was evaluated in five RCTs including CC patients [189][190][191][192][193][194] and in two RCTs including LC patients. 192,195 In all seven RCTs, HRQoL was markedly altered at baseline in both CC and LC patients, and improved after budesonide treatment. [196][197][198] Are there established metrics to measure disease activity and clinical remission in MC?…”
Section: Very Lowmentioning
confidence: 99%
“…Clinical response. A pooled analysis for clinical response in three studies 192,195,297 shows a statistically significant benefit for budesonide over placebo. Clinical remission was noted in 84% (43/51) of budesonide patients and 43% (19/44) of placebo patients (RR 1.89, 95% CI: 1.3-2.7), without heterogeneity (I 2 ¼ 0%) (see also Appendix D, supplementary material).…”
Section: Diagnosis Of MC What Is the Endoscopic Appearance Of Mc?mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, biologic (anti-tumour necrosis factor α) immunosuppressant drugs have been used in patients with refractory symptoms, with potentially encouraging results, but again these have not been assessed in clinical trials 45. The most recent clinical trials of mesalamine in patients with CC and LC have shown this drug to be no more effective than placebo 55 56…”
Section: Is a Highly Treatable Conditionmentioning
confidence: 99%